2020
DOI: 10.3329/baj.v23i1.50116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sunflower Residues and Herbicide on Weed Suppression, Grain Yield and Economics of Transplanted Aman Rice

Abstract: A field experiment was conducted at Agronomy Field Laboratory, Patuakhali Science and Technology University, Dumki, Patuakhali from July 2018 to November 2018 to evaluate the effect of sunflower residues and herbicides on the yield and economic performance of transplanted Aman rice. Weed control methods tested were T1 = weedy check (Unweeded control), T2 = Weed-free check by hand weeding twice, T3 = Pendimethalin, T4 = Pretilachlor, T5 = Butachlor, T6 = Pyrazosulfuron ethyl, T7 = Bensulfuron methyl + Acetachlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The highest number of grains panicle -1 (120.78) was recorded in weed-free treatment and Weedy check treatment gave the lowest no. of grains panicle -1 (78.85) in transplanted rice by Tanu et al (2020). These results are also the substantiating with the results of Acharya and Bhattacharya (2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The highest number of grains panicle -1 (120.78) was recorded in weed-free treatment and Weedy check treatment gave the lowest no. of grains panicle -1 (78.85) in transplanted rice by Tanu et al (2020). These results are also the substantiating with the results of Acharya and Bhattacharya (2013).…”
Section: Discussionsupporting
confidence: 89%
“…Islam et al, (2018) reported the lowest number of effective tiller hill -1 due to the severe crop weed competition in the weedy treatment whereas, the highest number was found in weed free treatment because of no crop-weed competition in T. Aman rice. The highest number of panicles m -2 (305.00) was recorded from weed free plots by manual weeding in transplanted rice (Tanu et al 2020). Maximum number of tiller hill -1 (16.36) was found in weed free treatment (C2W1) followed by C3W1 (15.67).…”
Section: Discussionmentioning
confidence: 98%